Optimal Programmed Intermittent Epidural Bolus Interval Timing When Using 10 mL of 0.1% Ropivacaine and 0.5 mcg/mL Sufentanil for Labor Analgesia in Patients Without Breakthrough Pain: A Prospective, Randomized Study - Xu DC; Ying J; Zhao J; Chen XD; Deng GP; Zhao YP; Xiao F (Dove Medical Press, 2024)
Ding-Chao Xu,1,* Jun Ying,2,* Jing Zhao,1 Xin-De Chen,1 Guo-Ping Deng,1 Yan-Ping Zhao,3 Fei Xiao3 1Department of Anesthesia, Jiashan First People's Hospital, Jiaxing City, People's Republic of China; 2Department of Anesthesia, Jiashan Maternity and Child Care Hospital, Jiaxing City, People's Republic of China; 3Department of Anesthesia, Jiaxing University Affiliated Women and Children Hospital, Jiaxing City, People's Republic of China*These authors contributed equally to this workCorrespondence: Fei Xiao; Yan-Ping Zhao, Department of Anesthesia, Jiaxing University Affiliated Women and Children Hospital, East Zhonghuang Road, Jiaxing City, People's Republic of China, Tel +86 573 83963131, Email 13706597501@163.com; 4921057876@qq.comBackground: Interval time, defined as the period of time that effective analgesia can be achieved without the need for patient-controlled epidural analgesia (PCEA), has been investigated as an important parameter for the design of programmed intermittent epidural bolus (PIEB) approaches to labor analgesia. PCEA approaches offer flexibility in the management of labor-related pain while minimizing the risk of patient overdose. Here, the optimal interval between PIEB boluses of 0.1% ropivacaine and 0.5 μg/mL sufentanil was evaluated while using revised criteria to define effective analgesia that allowed for the administration of a rescue PCEA bolus during these intervals.Methods: Participants were assigned at random to five different groups with PIEB intervals that ranged from 35 to 55 minutes. Labor epidural analgesia was initiated by administering 15mL of 0.1% ropivacaine with 0.5 μg/mL sufentanil over a 2-minute period. Analgesia was considered effective if there was no additional requirement for manual analgesia or an additional PCEA bolus beyond a maximum of one PCEA bolus between intervals during the first stage of labor. Probit regression analyses were used to estimate the effective PIEB intervals that achieved 50% (EI50) and 90% (EI90) success rates in patients.Results: The final analysis included 142 patients who underwent PIEB for maintaining analgesia during labor. Intervals of 55, 50, 45, 40, and 35 minutes were associated with analgesia efficacy odds of 82.8% (24/29), 86.2% (25/29), 96.3% (26/27), 100% (29/29), and 100% (28/28), respectively. The respective EI50 and EI90 intervals associated with patients not suffering from breakthrough pain were 62.9 (95% CI 57.2- 91.8) and 50.4 (95% CI 45.3- 54.9) minutes.Conclusion: Under the condition of this study, the optimal PIEB interval for the administration of 10 mL boluses of 0.1% ropivacaine and 0.5 μg/mL sufentanil is approximately 50 minutes.Keywords: ropivacaine, sufentanil, labor analgesia, epidural